ANALISIS PENGELOLAAN REKLAME PADA DINAS PENERANGAN JALAN DAN PENGELOLAAN REKLAME KOTA SEMARANG - Endah Rahayu Wijayanti; Endang Larasati; Titik Djumiarti (Journal of Public Policy and Management Review, 2013)
Funds needed to realize the development agenda in the region, its raised from Pendapatan Asli Daerah (PAD). One source of Pendapatan Asli Daerah (PAD) in the city of Semarang is through reclame, carried out by Dinas Penerangan Jalan dan Pengelolaan Reklame Kota SemarangThis study used an advanced management theory by George Terry which is Planning, Organizing, Actuating, and Controlling. Research approach use a type of descriptive research with qualitative methods. Data collection was conducted through in-depth interviews of the informants who have been determinedThe results of the study explained that the management of reclame in Semarang conducted by reclame field at the Dinas Penerangan Jalan dan Pengelolaan Reklame through three sections: structuring section, section arrangement, billing section, and licensing section. Management of billboards in the city of Semarang is not optimal due to weak supervision conducted. This happens because of non-performance on standard measurements and sizes oversight and planning is not conducted in accordance with the existing local regulation. Weak supervision due to a lack of organization and mobilization in the form of motivation given to the employee.